Morphological and ecological diversity of Amebelodontidae (Proboscidea, Mammalia) revealed by a Miocene fossil accumulation of an upper-tuskless proboscidean. (3rd August 2017) - Wang, Shi-Qi; Deng, Tao; Ye, Jie; He, Wen; Chen, Shan-Qin
Abstract : Amebelodontidae is the most taxonomically and morphologically diverse group of proboscideans. However, relative to the morphological variation of the mandible and mandibular tusks, ecological and phylogenetic differentiations within Amebelodontidae have been largely debated. Here we evaluate a middle Miocene fossil accumulation of a new amebelodontid, Aphanobelodon zhaoi gen. et sp. nov. This species lacks upper tusks, which is unique in elephantiforms. The mandible and mandibular tusk morphologies of A. zhaoi are similar to those of the genus Platybelodon, which is the typical representative of one of the two main amebelodontid branches (the other branch is represented by Amebelodon ). We suggest that Amebelodon potentially used its mandible and mandibular tusks to dig for food in relatively hard substrates; whereas Platybelodon is more specialized and possibly used its mandibular tusks for cutting soft vegetation. Aphanobelodon zhaoi morphology indicates that it is an offshoot of the platybelodont clade within Amebelodontidae, because it has primitive undifferentiated states of the mandible and mandibular tusks. Cladistic analysis indicates that Aphanobelodon, Platybelodon and Torynobelodon comprise a monophyletic group within Amebelodontidae. This study enhances our knowledge regarding proboscidean evolutionary history in terms of morphology, taxonomy and biology. http://zoobank.org/urn:lsid:zoobank.org:pub:8F30BAC7-4245-4952-BFCF-884E3DB839F6